Approximation of signals belonging to generalized Lipschitz class using -summability mean of Fourier series - Tejaswini Pradhan (Cogent Mathematics, 2016)
Degree of approximation of functions of different classes has been studied by several researchers by different summability methods. In the proposed paper, we have established a new theorem for the approximation of a signal (function) belonging to the $ W(L_{r},ξ (t)) $-class by $ (\overline{N},p_{n},q_{n})(E,s) $-product summability means of a Fourier series. The result obtained here, generalizes several known theorems.